Synthesis of Cystine-Stabilised Dicarba Conotoxin EpI: Ring-Closing Metathesis of Sidechain Deprotected, Sulfide-Rich Sequences - Amy L. Thomson; Andrea J. Robinson; Alessia Belgi (Marine Drugs, 2023)
Recombinant peptide synthesis allows for large-scale production of peptides with therapeutic potential. However, access to dicarba peptidomimetics via sidechain-deprotected sequences becomes challenging with exposed Lewis basicity presented by amine and sulfur-containing residues. Presented here is a combination of strategies which can be used to deactivate coordinative residues and achieve high-yielding Ru-catalyzed ring-closing metathesis. The chemistry is exemplified using α-conotoxin EpI, a native bicyclic disulfide-containing sequence isolated from the marine conesnail Conus episcopatus. Replacement of the loop I disulfide with E/Z–dicarba bridges was achieved with high conversion via solution-phase ring-closing metathesis of the unprotected linear peptide after simple chemoselective oxidation and ion-exchange masking of problematic functionality. Metathesis was also attempted in green solvent choices to further improve the sustainability of dicarba peptide synthesis.